Pengaruh Debt Default, Financial Distress, dan Auditor Switching Terhadap Penerimaan Opini Audit Going Concern - Lathifa, Nisrina Della; Nindito, Marsellisa; Yusuf, Muhammad (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
Researching infrastructure companies traded on the Indonesia Stock Exchange (BEI) in 2022 and 2023, this research will examine the impact of debt default, financial distress, and auditor switching on the approval of going concern audit opinions. A quantitative technique based on descriptive methodology was used in this investigation. Using IBM SPSS Version 29, this research used logistic regression analysis as its data analysis technique. This study found that the acceptance of going concern audit opinions is substantially affected solely by financial distress. There were no notable results from the debt default and auditor switching.